$$\sinh(x) = \frac{1}{2(e^x - e^{-x})}$$ $$\cosh(x) = \frac{1}{2(e^x + e^{-x}}$$ $$\tanh(x) = \frac{\sinh (x)}{\cosh (x)}$$

Prove: $$\frac{d(\tanh(x))}{dx} = \frac{1}{(\cosh x)^2}$$

I got the derivative for $\tanh(x)$ as: $$\left[ \frac{1}{2(e^x + e^{-x})}\right]^2 - \frac{{[ \frac{1}{2(e^x + e^{-x})}]^2}}{[ \frac{1}{2(e^x + e^{-x})}]^2}$$

  • 3
    $\begingroup$ Welcome to math.SE. Please read about proper typesetting in LaTeX and make sure your questions meet the general standards of the site - you will get used to the norm by reading a few of the questions. $\endgroup$ – Andrew Thompson Apr 5 '14 at 17:03

$$\dfrac{d(f/g)}{dx}=\dfrac{gf^\prime-fg^\prime}{g^2}$$ Set $f=\sinh,g=\cosh$ to get $$\dfrac{d\tanh}{dx}=\dfrac{\cosh\cdot\sinh^\prime-\sinh\cdot\cosh^\prime}{\cosh^2}$$ Now, $$\sinh^\prime=\dfrac{1}{2}(e^x+e^{-x})=\cosh\\ \cosh^\prime=\dfrac{1}{2}(e^x-e^{-x})=\sinh$$ Thus, $$\dfrac{d\tanh}{dx}=\dfrac{\cosh^2-\sinh^2}{\cosh^2}=1-\left(\dfrac{\sinh}{\cosh}\right)^2=1-\tanh^2$$ Now, $$\dfrac{1}{\cosh^2}=1-\tanh^2$$ (Proof: $$1-\dfrac{\sinh^2 x}{\cosh^2 x}= \dfrac{\cosh^2 x-\sinh^2 x}{\cosh^2 x}$$ Since $(\cosh^2 x) - (\sinh^2 x) = 1$, $$\dfrac{1}{\cosh^2 x} = {\operatorname{sech}^2 x} $$) Thus, $$\boxed{\dfrac{d\tanh}{dx}=1-\tanh^2=\dfrac{1}{\cosh^2 x}}$$


Observe that $$(a+b)^2-(a-b)^2=4ab$$

Set $a=e^x,b=e^{-x}$ and $\displaystyle \operatorname{sech}x=\frac1{\cosh x}=\frac2{e^x+e^{-x}}$


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.